Cleavable Biotin Probes for Labeling of Biomolecules via Azide−Alkyne Cycloaddition - Szychowski, Janek; Mahdavi, Alborz; Hodas, Jennifer J. L; Bagert, John D; Ngo, John T; Landgraf, Peter; Dieterich, Daniela C; Schuman, Erin M; Tirrell, David A (Journal of the American Chemical Society, 2010)
The azide−alkyne cycloaddition provides a powerful tool for bio-orthogonal labeling of proteins, nucleic acids, glycans, and lipids. In some labeling experiments, e.g., in proteomic studies involving affinity purification and mass spectrometry, it is convenient to use cleavable probes that allow release of labeled biomolecules under mild conditions. Five cleavable biotin probes are described for use in labeling of proteins and other biomolecules via azide−alkyne cycloaddition. Subsequent to conjugation with metabolically labeled protein, these probes are subject to cleavage with either 50 mM Na2S2O4, 2% HOCH2CH2SH, 10% HCO2H, 95% CF3CO2H, or irradiation at 365 nm. Most strikingly, a probe constructed around a dialkoxydiphenylsilane (DADPS) linker was found to be cleaved efficiently when treated with 10% HCO2H for 0.5 h. A model green fluorescent protein was used to demonstrate that the DADPS probe undergoes highly selective conjugation and leaves a small (143 Da) mass tag on the labeled protein after cleavage. These features make the DADPS probe especially attractive for use in biomolecular labeling and proteomic studies.